The Effectiveness of Using Werewolf Games to Enhance Speaking Skills - Muh.Hikmal Danial; Ibrahim Manda; Syahrir L; Andi Sadapotto; Sam Hermansyah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study investigates the effectiveness of the Werewolf game in improving the speaking skills of second-semester English Education students at Universitas Muhammadiyah Sidenreng Rappang. Speaking is one of the most essential language skills, yet many students face difficulties in fluency, confidence, and vocabulary usage. Traditional teaching methods often fail to actively engage students in meaningful communication. Therefore, implementing game-based learning, such as the Werewolf game, offers an interactive and enjoyable approach to language learning. This research employed a one-group pre-test and post-test pre-experimental design involving seven students. Participants engaged in structured speaking activities before and after the intervention. Data were analyzed using SPSS, revealing a significant improvement in students' speaking performance. The mean score increased from 54% to 83%, with a p-value of 0.006 (< 0.05), indicating a statistically significant impact. These findings suggest that incorporating the Werewolf game into speaking lessons can effectively enhance students’ participation, motivation, and confidence in expressing their ideas in English. The Werewolf game promotes real-time interaction, critical thinking, and spontaneous speech, which are crucial for developing communicative competence. By encouraging students to articulate their thoughts, respond to others, and negotiate meaning in a dynamic setting, the game fosters a more engaging and less anxiety-inducing environment compared to conventional methods.